UV-cured white ink as well as preparation method and application thereof

By using a combination of acrylate resin, free radical photoinitiator and multiple particle size fillers in UV cured white ink, the problem of insufficient reflectivity and photocuring depth in the prior art is solved, and the improvement of high reflectivity, deep light curing and product stability is achieved, and it is suitable for the application of a variety of reflective materials.

CN119859433APending Publication Date: 2025-04-22ENOVATE3D (HANGZHOU) TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510147515.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing UV cured white inks are difficult to take into account both reflectivity and light curing depth, the product has poor stability and a long curing time, which cannot meet the needs of high-performance reflective materials.

Method used

The photocuring complex of acrylate A and acrylate B is used, combining free radical photoinitiators and tertiary amine coinitiators, using a variety of fillers of different particle sizes, and adding additives such as anti-settling agents, to improve the adhesion, strength and stability of the material through these combinations.

Benefits of technology

High-performance UV cured white ink with reflectivity greater than 94%, whiteness greater than 70%, and photocuring depth greater than 200μm is achieved. The product stability is improved and the curing time is shortened to 25 seconds. It is suitable for surface coating treatment of a variety of reflective materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859433A_ABST
    Figure CN119859433A_ABST
Patent Text Reader

Abstract

The invention discloses UV-cured white ink as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials. The UV-cured white ink comprises the following components in parts by weight: 100 parts of acrylate A, 10-40 parts of acrylate B, 0.1-2 parts of a free radical photoinitiator, 20-70 parts of filler and 0.5-10 parts of auxiliaries, the auxiliaries comprise an auxiliary initiator and an anti-settling agent, the auxiliary initiator is a tertiary amine auxiliary initiator, and the anti-settling agent is an anti-settling agent. The acrylate A is selected from at least one of aliphatic polyurethane acrylate, polyurethane modified epoxy acrylate and amine modified epoxy acrylate, and the acrylate B is selected from at least one of methacrylic acid phosphate, isobornyl methacrylate and tripropylene glycol diacrylate. The UV-cured white ink disclosed by the invention has both product reflectivity and photocuring depth, is excellent in long-term storage stability and can be rapidly cured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a UV curable white ink and a preparation method and application thereof. Background Art

[0002] Ultraviolet light curing (UV curing) white ink (abbreviated as "UV white oil") can be quickly cured by UV light irradiation and is suitable for surface coating treatment of various reflective materials. With the rapid development of display technology and lighting technology, the optical properties of material surfaces are increasingly required. Especially in the application of reflective materials, the coating on the surface of the material is required to have excellent reflectivity to improve the efficiency of light utilization. Currently, commonly used coatings include solvent-based white oil, water-based white oil, etc., but there are still the following technical problems:

[0003] (1) Most of the UV white oil materials reflect most of the ultraviolet light due to their certain reflectivity, resulting in insufficient curing depth, that is, it is impossible to take both reflectivity and light curing depth into account at the same time. In addition, during the UV curing process, the surface is easily cured while the bottom is not cured, resulting in the material having a narrow application range and usage scenarios and a low degree of curing. In addition, the reflectivity of most white materials in the prior art is still less than 90%. During use, the reflectivity of light is limited, which affects the utilization rate of light and results in high energy consumption.

[0004] (2) Most existing UV white inks use resins with high unsaturated bond content, which causes the material to break easily in high temperature environments, turn yellow easily, and affect product stability. In addition, due to the use scenario, low-viscosity (<2000cp) products often lead to poor filler stability, easy sedimentation, and inability to store for a long time (titanium dioxide gradually settles when placed at room temperature for ≥48 hours).

[0005] (3) Most of the existing high-reflective materials are thermal curing or light-curing and thermal-curing dual-curing systems. They require heating during the curing process, which may have a certain impact on the products or components. In addition, the required heating time is long, the energy consumption is high, and the storage conditions are demanding, which further leads to problems of low efficiency and high energy consumption costs.

[0006] It can be seen that UV curing coatings have attracted widespread attention due to their high efficiency and environmental protection characteristics, but existing UV curing white oils usually have insufficient reflectivity, insufficient light curing depth, poor product stability, or are prone to unevenness during the curing process, which cannot meet the needs of high-performance reflective materials. Therefore, it is urgent to provide a UV white ink with high reflectivity and light curing depth, good product stability, fast curing and uniform coating. Summary of the invention

[0007] The main purpose of the present invention is to provide a UV curable white ink and a preparation method and application thereof, so as to solve the problems in the prior art that UV curable white ink is difficult to balance reflectivity and light curing depth, has poor product stability and requires a long curing time.

[0008] In a first aspect, the present invention provides a UV curable white ink comprising, by weight:

[0009] Acrylate A: 100 parts;

[0010] Acrylate B: 10-40 parts;

[0011] Free radical photoinitiator: 0.1-2 parts;

[0012] Filler: 20-70 parts;

[0013] Additives: 0.5-10 parts;

[0014] The auxiliary agent includes an auxiliary initiator and an anti-settling agent, wherein the auxiliary initiator is a tertiary amine auxiliary initiator; the auxiliary initiator can interact with the free radical photoinitiator to play a role of deep curing during the curing process and improve the photoinitiation efficiency during curing;

[0015] The acrylate A is selected from at least one of aliphatic polyurethane acrylate, polyurethane-modified epoxy acrylate, and amine-modified epoxy acrylate;

[0016] The acrylate B is selected from at least one of methacrylate phosphate (HEMP), isobornyl methacrylate (IBOA), and tripropylene glycol diacrylate (TPGDA);

[0017] The complex obtained by photocuring the above acrylate A and acrylate B can effectively improve the adhesion and strength of the material. At the same time, since the unsaturated bonds in acrylate A can participate in the curing as reaction points, there are no unsaturated bonds in the obtained cured product, which makes the cured product have higher yellowing resistance.

[0018] Furthermore, the tertiary amine co-initiator is selected from at least one of isooctyl p-dimethylaminobenzoate (EHA), ethyl 4-dimethylaminobenzoate (EDAB), and methyldiethanolamine (MDEA).

[0019] Furthermore, the viscosity of the acrylate A is 5000-20000 cp, and the viscosity of the acrylate B is 50-2000 cp.

[0020] Furthermore, the free radical photoinitiator is selected from at least one of quinone photoinitiators, 184 (1-hydroxy-cyclohexyl benzophenone), 784 (bis-titaniamonene), and 819 (bisphenylphosphine oxide); more preferably, the free radical photoinitiator is selected from quinone photoinitiators.

[0021] Furthermore, the filler is selected from at least one of titanium dioxide, zinc oxide, and barium sulfate; preferably, the filler is selected from titanium dioxide, zinc oxide, or barium sulfate with a particle size of 0.1-5 μm, and the mass ratio of fillers with different particle sizes is (0.1-0.5 μm): (0.5-1.0 μm): (1.0-2.0 μm) = (4-7): (2-4): (1-2). The combination of fillers with various particle sizes can effectively avoid their agglomeration and improve their dispersibility in the resin. Fillers with different particle sizes can improve the surface diffuse reflection and further improve the reflectivity of the material, which is significantly higher than the reflectivity of UV-curable white ink prepared with fillers with a single particle size.

[0022] More preferably, the filler is selected from rutile titanium dioxide. The absorption, scattering and reflection of ultraviolet light by rutile titanium dioxide are weaker than those by anatase titanium dioxide, which is more conducive to photocuring. At the same time, the absorption rate of UV light by rutile titanium dioxide is generally lower than that of anatase titanium dioxide, and the hiding power and tinting power are also higher than those of anatase titanium dioxide, and it is not easy to pulverize.

[0023] Furthermore, the anti-settling agent is selected from at least one of SiTengda-13956 (polyamide wax), BP186 (organic bentonite), and 150X (ultrafine matting powder / fumed silica). The above three anti-settling agents can improve the anti-settling property of the material to varying degrees.

[0024] Furthermore, the reflectivity of the UV-curable white ink is greater than 94%, the whiteness value is greater than 70%, the curing depth is greater than or equal to 200 μm, the difference in whiteness value before and after monitoring for 1000 hours under double 85 conditions is less than 3%, and the UV light curing time is less than or equal to 25 seconds.

[0025] Furthermore, the maximum absorption wavelength range of the free radical photoinitiator is about 470nm, and the absorption wavelength range of the filler is less than 395nm. After absorbing light energy, the free radical photoinitiator produces hydrogen abstraction with the co-initiator, initiating free radical polymerization and effectively improving its curing depth, while cleverly avoiding the absorption wavelength range of the filler. This curing agent can effectively utilize light that cannot be absorbed by titanium dioxide during the curing process, thereby achieving a higher curing depth.

[0026] In a second aspect, the present invention provides a method for preparing a UV-curable white ink, comprising the following steps:

[0027] Mixing acrylate A and acrylate B in proportion to obtain a first mixed material;

[0028] Adding a photoinitiator, a co-initiator and an anti-settling agent to the first mixed material to obtain a second mixed material;

[0029] adding filler to the second mixed material to obtain a third mixed material;

[0030] The third mixed material is ground and filtered to obtain the UV curable white ink.

[0031] Furthermore, the UV curable white ink is prepared under a 570nm-590nm yellow light room.

[0032] Furthermore, fillers with different particle sizes are first mixed evenly and then added into the second mixed material.

[0033] Furthermore, the stirring speed of the first mixture is 1300-1700RPM, and the stirring time is 3-10min; the stirring speed of the second mixture is 1000-1700RPM, and the stirring time is 3-10min; the stirring speed of the third mixture is 1000-1700RPM, and the stirring time is 3-10min; the size of the third mixture after grinding is less than 10μm.

[0034] In a third aspect, the present invention provides the application of the UV-curable white ink in Mini LED backlight coatings, LED displays, printed electronics, and LED lighting.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The UV curable white ink uses a free radical photoinitiator and a special co-initiator in combination, wherein the free radical photoinitiator has a maximum absorption wavelength of about 470 nm. After absorbing light energy, it reacts with the co-initiator to generate hydrogen abstraction, thereby initiating free radical polymerization and effectively improving its curing depth. At the same time, it cleverly avoids the absorption wavelength range of the filler. During the curing process, this curing agent can effectively utilize light that cannot be absorbed by the filler, thereby achieving a maximum curing depth of 300 μm, which is beneficial to improving the application scenarios and versatility of the material.

[0037] (2) The UV curable white ink uses a variety of fillers with different particle sizes. The fillers with different particle sizes can effectively improve the dispersibility and stability of the filler particles in the white ink and enhance the light reflection effect. The white ink prepared by the present invention has a high reflectivity of more than 94% and a high whiteness of more than 70%, which is more than 4% higher than the reflectivity of the white ink prepared by using fillers with uniform particle size, which is conducive to further improving the utilization rate of light and reducing energy consumption.

[0038] (3) The UV curable white ink is compounded with two special acrylic resins. It can be judged from the whiteness test data before and after the aging test that most of the double bonds are used as reaction points for reaction. The combination of the two resins described in the present invention can make the final material more stable after curing, and is not easily affected by ultraviolet rays or high temperatures to cause aging or bond breaking, thereby improving its yellowing resistance and greatly improving product stability;

[0039] (4) The UV-curable white ink can be quickly cured within 25 seconds by UV light irradiation, and has excellent optical reflection performance and light curing depth. It is suitable for surface coating treatment of various reflective materials such as optical devices, displays, lighting equipment, etc., and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 is a schematic diagram of a white ink film layer;

[0041] Figure 2 Figure 2 is a graph of the absorbance of different types of titanium dioxide. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0043] As described in the background technology section of the present invention, existing UV curable white inks usually have insufficient reflectivity, insufficient light curing depth, poor product stability, or are prone to unevenness during the curing process, and cannot meet the needs of high-performance reflective materials. A first aspect of the present invention provides a UV curable white ink, which comprises, by weight:

[0044] Acrylate A: 100 parts;

[0045] Acrylate B: 10-40 parts;

[0046] Free radical photoinitiator: 0.1-2 parts;

[0047] Filler: 20-70 parts;

[0048] Additives: 0.5-10 parts;

[0049] The auxiliary agent includes a co-initiator and an anti-settling agent, wherein the co-initiator is a tertiary amine co-initiator; the acrylate A is selected from at least one of aliphatic polyurethane acrylate, polyurethane-modified epoxy acrylate, and amine-modified epoxy acrylate; the acrylate B is selected from at least one of methyl methacrylate phosphate (HEMP), isobornyl methacrylate (IBOA), and tripropylene glycol diacrylate (TPGDA).

[0050] In a preferred embodiment, the tertiary amine co-initiator is selected from at least one of isooctyl p-dimethylaminobenzoate (EHA), ethyl 4-dimethylaminobenzoate (EDAB), and methyldiethanolamine (MDEA).

[0051] In a preferred embodiment, when the auxiliary initiator is selected from isooctyl p-dimethylaminobenzoate and the free radical photoinitiator is selected from quinone photoinitiators, the UV curable white ink prepared by using the two in combination has a better curing effect.

[0052] In a preferred embodiment, the viscosity of the acrylate A is 5000-20000 cp, and the viscosity of the acrylate B is 50-2000 cp. The use of the two resins makes the viscosity of the final formula in a relatively low range after mixing, so the viscosity of the two acrylate resins cannot be too high.

[0053] In a preferred embodiment, the free radical photoinitiator is selected from at least one of quinone photoinitiators, 184 (1-hydroxy-cyclohexyl benzophenone), 784 (bis-titaniamonene), and 819 (bisphenylphosphine oxide); more preferably, the free radical photoinitiator is selected from quinone photoinitiators.

[0054] In a preferred embodiment, the filler is selected from at least one of titanium dioxide, zinc oxide, and barium sulfate; more preferably, the filler is selected from titanium dioxide, zinc oxide, and barium sulfate with a plurality of different particle sizes having a particle size of 0.1-5 μm, and the mass ratio of fillers with different particle sizes is (0.1-0.5 μm): (0.5-1.0 μm): (1.0-2.0 μm) = (4-7): (2-4): (1-2).

[0055] In a preferred embodiment, the filler is selected from rutile titanium dioxide, such as Figure 2 As shown, the absorption, scattering and reflection of ultraviolet light by rutile titanium dioxide are weaker than those by anatase titanium dioxide, which is more conducive to photocuring. At the same time, the absorption rate of UV light by rutile titanium dioxide is generally lower than that of anatase titanium dioxide, and the hiding power and tinting power are also higher than those of anatase titanium dioxide, and it is not easy to pulverize. The anti-settling agent is selected from at least one of Si Tengda-13956 (polyamide wax), BP186 (organic bentonite), and 150X (ultrafine matting powder / fumed silica).

[0056] In a preferred embodiment, the maximum absorption wavelength range of the free radical photoinitiator is about 470 nm (generally 400-500 nm), and the absorption wavelength range of the filler is <395 nm.

[0057] Furthermore, the reflectivity of the UV-curable white ink is greater than 94%, the whiteness value is greater than 70%, the curing depth is greater than or equal to 200 μm, the difference in whiteness value before and after monitoring for 1000 hours under double 85 conditions is less than 3%, and the UV light curing time is less than or equal to 25 seconds.

[0058] A second aspect of the present invention provides a method for preparing a UV-curable white ink, comprising the following steps:

[0059] Mixing acrylate A and acrylate B in proportion to obtain a first mixed material;

[0060] Adding a photoinitiator, a co-initiator and an anti-settling agent to the first mixed material to obtain a second mixed material;

[0061] adding filler to the second mixed material to obtain a third mixed material;

[0062] The third mixed material is ground and filtered to obtain the UV curable white ink.

[0063] In a preferred embodiment, the UV curable white ink is prepared under 570nm-590nm yellow light room.

[0064] In a preferred embodiment, fillers with different particle sizes are first mixed evenly and then added to the second mixed material.

[0065] In a preferred embodiment, the stirring speed for obtaining the first mixture is 1300-1700RPM, and the stirring time is 3-10min; the stirring speed for obtaining the second mixture is 1000-1700RPM, and the stirring time is 3-10min; the stirring speed for obtaining the third mixture is 1000-1700RPM, and the stirring time is 3-10min; the size of the third mixture after grinding is less than 10μm.

[0066] Typically, but not limiting, the UV curable white ink comprises, by weight: 100 parts of acrylate A, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or any two of the ranges of acrylate B, 0.1 parts, 0.4 parts, 0.7 parts, 1.0 parts, 1.3 parts, 1.6 parts, 2.0 parts or any two of the ranges of free radical photoinitiator, 20 parts, 30 parts , 40 parts, 50 parts, 60 parts, 70 parts or a range consisting of any two of them; 0.5 parts, 1.0 parts, 1.5 parts, 2.0 parts, 2.5 parts, 3.0 parts, 3.5 parts, 4.0 parts, 4.5 parts, 5.0 parts, 5.5 parts, 6.0 parts, 6.5 parts, 7.0 parts, 7.5 parts, 8.0 parts, 8.5 parts, 9.0 parts, 9.5 parts, 10 parts or a range consisting of any two of them.

[0067] Typically but not limiting, the viscosity of acrylate A is 3000cp, 5000cp, 7000cp, 9000cp, 11000cp, 13000cp, 15000cp, 17000cp, 20000cp or a range consisting of any two of them, and the viscosity of acrylate B is 50cp, 500cp, 1000cp, 1500cp, 2000cp or a range consisting of any two of them.

[0068] Typically but not limiting, the weight portion of the co-initiator is 0.5 part, 1.0 part, 1.5 parts, 2.0 parts or a range consisting of any two of them, and the weight portion of the anti-settling agent is 0.2 part, 0.8 part, 1.4 parts, 2.0 parts, 2.6 parts, 3.2 parts, 3.8 parts, 4.4 parts, 5.0 parts or a range consisting of any two of them.

[0069] The preparation of UV curable white ink in the following examples was carried out under a yellow light room with a wavelength of 570 nm. Figure 1 Shown is a schematic diagram of a white ink film layer.

[0070] Example 1

[0071] 100g of aliphatic polyurethane acrylate resin with a viscosity of 5000cp and 20g of methyl methacrylate phosphate resin with a viscosity of 50cp were stirred evenly using a homogenizer at 1500rpm, and then 1g of camphorquinone, 1g of EHA, and 0.5g of Si Tengda-13956 were added and stirred again using a homogenizer at 1500rpm. Then, 50g of titanium dioxide with a particle size ratio of 0.1μm:0.5μm:1μm=5:3:2 was added and stirred at 2000rpm for 3min, followed by high-precision three-roll mill grinding to a size of less than 10μm, and finally pressure filtration was performed to obtain a UV white ink with a viscosity of about 2000cp.

[0072] The performance of the UV white ink was tested, and the results showed that the ink film thickness was 300 μm and fully cured, with a reflectivity of 94.21% and a whiteness of 73.07%. The reflectivity at a film thickness of 70 μm was 94.13%, and the whiteness was 72.88%. After baking at 150°C for 2 hours, the whiteness was 71.63%, the yellowing resistance was excellent, the anti-settling performance was excellent, the ISO grade was 0, and the UV light was cured for 25 seconds.

[0073] Example 2

[0074] The difference from Example 1 is that 150X is used as an anti-settling agent, and the remaining steps are the same. The preparation method is as follows:

[0075] 100g of aliphatic polyurethane acrylate resin with a viscosity of 5000cp and 20g of methyl methacrylate phosphate resin with a viscosity of 50cp were stirred evenly using a homogenizer at 1500rpm, and then 1g of camphorquinone, 1g of EHA, and 0.5g of 150X were added and stirred again using a homogenizer at 1500rpm, and then 50g of titanium dioxide with a particle size of 0.1-5μm was added and stirred at 2000rpm for 3min, followed by high-precision three-roll mill grinding to a size of less than 10μm, and finally pressure filtration to obtain a UV white ink with a viscosity of about 2013cp.

[0076] The performance of the UV white ink was tested, and the results showed that the ink film thickness was 300 μm and fully cured, with a reflectivity of 94.18%, a whiteness of 73.04%, a reflectivity of 94.11% at a film thickness of 70 μm, a whiteness of 72.86%, a whiteness of 70.33% after baking at 150°C for 2 hours, excellent yellowing resistance, excellent anti-settling performance, ISO grade: 0, and UV light curing for 25 seconds.

[0077] Example 3

[0078] The difference from Example 1 is that 784 is used in combination with EHA as a curing agent, and the remaining steps are the same. The preparation method is as follows:

[0079] 100g of aliphatic polyurethane acrylate resin with a viscosity of 5000cp and 20g of methyl methacrylate phosphate resin with a viscosity of 50cp were stirred evenly using a homogenizer at 1500rpm, and then 1g of 784, 1g of EHA, and 0.5g of Si Tengda-13956 were added, and stirred again using a homogenizer at 1500rpm. Then, 50g of titanium dioxide with a particle size ratio of 0.1μm:0.5μm:1μm=5:3:2 was added, stirred at 2000rpm for 3min, and then ground with a high-precision three-roll mill to a size less than 10μm. Finally, it was filtered under pressure to obtain a UV white ink with a viscosity of about 2010cp.

[0080] The performance of the UV white ink was tested, and the results showed that the ink film thickness was 200 μm and fully cured, with a reflectivity of 94.15% and a whiteness of 72.63%. The reflectivity was 94.03% and the whiteness was 72.11% at a film thickness of 70 μm. After baking at 150°C for 2 hours, the whiteness was 70.86%, the yellowing resistance was excellent, the anti-settling performance was excellent, the ISO grade was 0, and the UV light was cured for 25 seconds.

[0081] Example 4

[0082] The difference from Example 3 is that EDAB is used instead of EHA as the co-initiator, and the remaining steps are the same. The preparation method is as follows:

[0083] 100g of aliphatic polyurethane acrylate resin with a viscosity of 5000cp and 20g of methyl methacrylate phosphate resin with a viscosity of 50cp were stirred evenly using a homogenizer at 1500rpm, and then 1g of 784, 1g of EDAB, and 0.5g of Si Tengda-13956 were added, and stirred again using a homogenizer at 1500rpm. Then, 50g of titanium dioxide with a particle size ratio of 0.1μm:0.5μm:1μm=5:3:2 was added, stirred at 2000rpm for 3min, and then ground with a high-precision three-roll mill to a size less than 10μm. Finally, it was filtered under pressure to obtain a UV white ink with a viscosity of about 2010cp.

[0084] The performance of the UV white ink was tested, and the results showed that the ink film thickness was 200 μm and fully cured, with a reflectivity of 94.05% and a whiteness of 72.03%. The reflectivity was 94.03% and the whiteness was 72.01% at a film thickness of 70 μm. After baking at 150°C for 2 hours, the whiteness was 70.66%, the yellowing resistance was excellent, the anti-settling performance was excellent, the ISO grade was 0, and the UV light was cured for 25 seconds.

[0085] Example 5

[0086] The difference from Example 3 is that MDEA is used instead of EHA as the co-initiator, and the other steps are the same. The preparation method is as follows:

[0087] 100g of aliphatic polyurethane acrylate resin with a viscosity of 5000cp and 20g of methyl methacrylate phosphate resin with a viscosity of 50cp were stirred evenly using a homogenizer at 1500rpm, and then 1g of 784, 1g of MDEA, and 0.5g of Si Tengda-13956 were added, and stirred again using a homogenizer at 1500rpm. Then, 50g of titanium dioxide with a particle size ratio of 0.1μm:0.5μm:1μm=5:3:2 was added, stirred at 2000rpm for 3min, and then ground with a high-precision three-roll mill to a size less than 10μm. Finally, it was filtered under pressure to obtain a UV white ink with a viscosity of about 2010cp.

[0088] The performance of the UV white ink was tested, and the results showed that the ink film thickness was 250 μm and fully cured, with a reflectivity of 94.03% and a whiteness of 71.95%. The reflectivity was 94.01% and the whiteness was 71.91% at a film thickness of 70 μm. After baking at 150°C for 2 hours, the whiteness was 70.53%, the yellowing resistance was excellent, the anti-settling performance was excellent, the ISO grade was 0, and the UV light was cured for 25 seconds.

[0089] Example 6

[0090] The difference from Example 1 is that the added mass of methacrylate phosphate resin is 10 g, and the other steps are the same.

[0091] Example 7

[0092] The difference from Example 1 is that the added mass of methacrylate phosphate resin is 40 g, and the other steps are the same.

[0093] Example 8

[0094] The difference from Example 1 is that the added amount of camphorquinone is 0.1 g, and the other steps are the same.

[0095] Example 9

[0096] The difference from Example 1 is that the added amount of camphorquinone is 2 g, and the other steps are the same.

[0097] Example 10

[0098] The difference from Example 1 is that the added amount of EHA is 0.5 g, and the other steps are the same.

[0099] Embodiment 11

[0100] The difference from Example 1 is that the added amount of EHA is 2 g, and the other steps are the same.

[0101] Example 12

[0102] The difference from Example 1 is that the added amount of SiTengda-13956 is 0.2 g, and the other steps are the same.

[0103] Example 13

[0104] The difference from Example 1 is that the added amount of SiTengda-13956 is 5 g, and the other steps are the same.

[0105] Embodiment 14

[0106] The difference from Example 1 is that the amount of titanium dioxide added is 20 g, and the other steps are the same.

[0107] Embodiment 15

[0108] The difference from Example 1 is that the amount of titanium dioxide added is 70 g, and the other steps are the same.

[0109] Comparative Example 1

[0110] The difference from Example 1 is that no co-initiator is added, only camphorquinone is used as a curing agent, and the remaining steps are the same. The preparation method is as follows:

[0111] 100g of aliphatic polyurethane acrylate resin with a viscosity of 5000cp and 20g of methyl methacrylate phosphate resin with a viscosity of 50cp were stirred evenly using a homogenizer at 1500rpm, and then 1g of camphorquinone and 0.5g of Siltenda-13956 were added, and stirred again using a homogenizer at 1500rpm. Then, 50g of titanium dioxide with a particle size ratio of 0.1μm:0.5μm:1μm=5:3:2 was added and stirred at 2000rpm for 3min, and then ground with a high-precision three-roll mill to a size less than 10μm. Finally, it was filtered under pressure to obtain a UV white ink with a viscosity of about 1989cp.

[0112] The performance of the UV white ink was tested, and the results showed that the ink film thickness was 150 μm and fully cured, the reflectivity was 94.00%, the whiteness was 73.01%, the whiteness was 71.53% after baking at 150° C. for 2 hours, the yellowing resistance was excellent, the anti-settling performance was excellent, the ISO grade was 0, and the UV light was cured for 25 seconds.

[0113] Comparative Example 2

[0114] The difference from Example 1 is that only one filler with a particle size of 0.1 μm is added, and the remaining steps are the same. The preparation method is as follows:

[0115] 100g of aliphatic polyurethane acrylate resin with a viscosity of 5000cp and 20g of methyl methacrylate phosphate resin with a viscosity of 50cp were stirred evenly using a homogenizer at 1500rpm, and then 1g of camphorquinone, 1g of EHA, and 0.5g of Silicon Tengda-13956 were added and stirred again using a homogenizer at 1500rpm, and then 50g of titanium dioxide with a particle size of 0.1μm was added and stirred at 2000rpm for 3min, followed by high-precision three-roll mill grinding to a size of less than 10μm, and finally pressure filtration was performed to obtain a UV white ink with a viscosity of about 2056cp.

[0116] The performance of the UV white ink was tested, and the results showed that the ink film thickness was 300 μm and fully cured, with a reflectivity of 90.12% and a whiteness of 70.22%. The reflectivity at a film thickness of 70 μm was 89.77%, and the whiteness was 69.64%. After baking at 150°C for 2 hours, the whiteness was 67.38%, the yellowing resistance was excellent, the anti-settling performance was excellent, the ISO grade was 0, and the UV light was cured for 25 seconds.

[0117] Comparative Example 3

[0118] The difference from Example 1 is that only one filler with a particle size of 5 μm is added, and the remaining steps are the same. The preparation method is as follows:

[0119] 100g of aliphatic polyurethane acrylate resin with a viscosity of 5000cp and 20g of methyl methacrylate phosphate resin with a viscosity of 50cp were stirred evenly using a homogenizer at 1500rpm, and then 1g of camphorquinone, 1g of EHA, and 0.5g of Silicon Tengda-13956 were added and stirred again using a homogenizer at 1500rpm. Then, 50g of titanium dioxide with a particle size of 5μm was added and stirred at 2000rpm for 3min, followed by high-precision three-roll mill grinding to a size of less than 10μm. Finally, it was filtered under pressure to obtain a UV white ink with a viscosity of about 2077cp.

[0120] The performance of the UV white ink was tested, and the results showed that the ink film thickness was 300 μm and fully cured, with a reflectivity of 91.12% and a whiteness of 68.32%. The reflectivity was 90.69% and the whiteness was 67.54% at a film thickness of 70 μm. After baking at 150°C for 2 hours, the whiteness was 66.52%, the yellowing resistance was excellent, the anti-settling performance was excellent, the ISO grade was 0, and the UV light was cured for 25 seconds.

[0121] Comparative Example 4

[0122] The difference from Example 1 is that the aliphatic polyurethane acrylate resin is replaced by an aromatic polyurethane acrylate resin, and the remaining steps are the same. The specific preparation method is as follows:

[0123] 100g of aromatic polyurethane acrylate resin with a viscosity of 5500cp and 20g of methyl methacrylate phosphate resin with a viscosity of 50cp were stirred evenly using a homogenizer at 1500rpm, and then 1g of camphorquinone, 1g of EHA, and 0.5g of Silicon Tengda-13956 were added and stirred again using a homogenizer at 1500rpm. Then, 50g of titanium dioxide with a particle size of 0.1-5μm was added and stirred at 2000rpm for 3min, and then ground with a high-precision three-roll mill to a size less than 10μm. Finally, it was filtered under pressure to obtain a UV white ink with a viscosity of 2230cp.

[0124] The performance of the UV white ink was tested, and the results showed that the ink film thickness was 300 μm and fully cured, with a reflectivity of 93.67% and a whiteness of 72.77%. The reflectivity at a film thickness of 70 μm was 93.36%, and the whiteness was 72.53%. After baking at 150°C for 2 hours, the whiteness was 50.69%, the yellowing resistance was unqualified, the anti-settling performance was excellent, the ISO grade was 0, and the UV light was cured for 25 seconds.

[0125] Comparative Example 5

[0126] The difference from Example 1 is that the common TPO (2,4,6-trimethylbenzoyl-diphenylphosphine oxide) on the market is used in combination with 1173 (2-hydroxy-2-methyl-phenylacetone-1) as a curing agent, and the remaining steps are the same. The preparation method is as follows:

[0127] 100g of aliphatic polyurethane acrylate resin with a viscosity of 5000cp and 20g of methyl methacrylate phosphate resin with a viscosity of 50cp were stirred evenly using a homogenizer at 1500rpm, and then 1g of TPO, 1g of 1173, and 0.5g of Si Tengda-13956 were added, and stirred again using a homogenizer at 1500rpm. Then, 50g of titanium dioxide with a particle size ratio of 0.1μm:0.5μm:1μm=5:3:2 was added, stirred at 2000rpm for 3min, and then ground with a high-precision three-roll mill to a size less than 10μm. Finally, it was filtered under pressure to obtain a UV white ink with a viscosity of about 2015cp.

[0128] The performance of the UV white ink was tested, and the results showed that the ink curing depth was insufficient, and only 10 μm could be fully cured. The reflectivity was 55.36%, and the reflectivity was much lower than expected due to the reduction in film thickness. The whiteness was 54.27%, and the whiteness was 27.66% after baking at 150°C for 2 hours. The yellowing resistance was unqualified, the anti-settling performance was excellent, ISO grade: 0, and UV light curing was 25 seconds.

[0129] Comparative Example 6

[0130] The difference from Example 1 is that ITX (thioxanthone) is used in combination with EDAB (ethyl 4-dimethylaminobenzoate) as a curing agent, and the remaining steps are the same. The preparation method is as follows:

[0131] 100g of aliphatic polyurethane acrylate resin with a viscosity of 5000cp and 20g of methyl methacrylate phosphate resin with a viscosity of 50cp were stirred evenly using a homogenizer at 1500rpm, and then 1g of ITX, 1g of EDAB, and 0.5g of Si Tengda-13956 were added and stirred again using a homogenizer at 1500rpm. Then, 50g of titanium dioxide with a particle size ratio of 0.1μm:0.5μm:1μm=5:3:2 was added and stirred at 2000rpm for 3min, followed by high-precision three-roll mill grinding to a size of less than 10μm, and finally pressure filtration to obtain a UV white ink with a viscosity of about 2007cp.

[0132] The performance test of the UV white ink showed that the curing depth was lower than expected, and only 20 μm could be fully cured. The reflectivity was 65.77%. Also due to the reduction in film thickness, the reflectivity was much lower than expected. The whiteness was 57.66%, and the whiteness was 37.86% after baking at 150°C for 2 hours. The yellowing resistance was unqualified, the anti-settling performance was excellent, ISO grade: 0, and UV light curing was 25 seconds.

[0133] The preparation method of the coating of the above embodiment and comparative example is as follows: first, the flat substrate is ultrasonically cleaned with an organic solvent such as ethanol to remove the oil on the surface. After cleaning, the substrate is placed in a 100°C oven for 30 minutes to completely remove the solvent. After the substrate is cooled to room temperature, a 3D printing device is used to print white ink into an ink coating of a desired thickness.

[0134] Then under the mercury lamp 1000mw / cm 2 The power was irradiated for 30 seconds, and the following properties of the ink coating were tested:

[0135] The performance test method of the highly reflective white ink is:

[0136] Viscosity: Use a Brookfield viscometer to test the viscosity of white ink at 25°C room temperature every week for 4 weeks, and determine the viscosity stability of the white ink by the change in viscosity.

[0137] Reflectivity: The reflectivity value of the white ink coating was tested using the Color Spectrum DS-700D spectrophotometer;

[0138] Whiteness: Use Shanghai Yuefeng SBDY-3 whiteness meter to test the whiteness value of white ink coating;

[0139] Yellowing resistance: Place the cured white ink sample in a double 85 aging test box at 85℃ / 85%RH for 1000h, and then use Shanghai Yuefeng SBDY-3 whiteness meter to test the whiteness. The aging resistance is judged by the change of whiteness value. If the difference of whiteness before and after heating is less than 3%, it is excellent; if 3%<difference<8%, it is good; if the difference is greater than 8%, it is unqualified.

[0140] Anti-settling performance: After standing for 7 days, take 5cc of the upper material and compare its mass with that of the standard sample. If the difference is less than 5%, the anti-settling performance is excellent; if 5% < difference < 10%, the anti-settling performance is good; if the difference is greater than 10%, the anti-settling performance is unqualified;

[0141] 100-grid test: Use a 100-grid knife to draw 10×10 (100) 1mm×1mm small grids on the surface of the test sample. Each line should be deep enough to reach the bottom layer of the paint. Use a brush to clean the debris in the test area. Use 3M 600 tape or tape of equivalent effectiveness to firmly stick to the small grid to be tested, and use an eraser to rub the tape vigorously to increase the contact area and strength between the tape and the tested area. Grasp one end of the tape with your hand and quickly tear off the tape in the vertical direction (90°). Perform the same test twice at the same location. Use the evaluation criteria in standard ISO 2409 to determine whether the coating is fully cured.

[0142] Table 1 Whiteness change data before and after aging

[0143]

[0144] Table 2 Anti-settling test data table

[0145]

[0146] From the comparison of the data in Table 1, it can be seen that in Comparative Examples 5 and 6, the maximum absorption wavelength of the photoinitiator overlaps with the absorption range of titanium dioxide, resulting in a low degree of curing; from Comparative Example 4, it is known that the use of a resin with a higher unsaturated bond will result in lower yellowing resistance, because a higher concentration of unsaturated bonds will result in the final cured product containing more unsaturated bonds, and these unsaturated bonds will be chain-interrupted in the yellowing resistance test, thereby causing the product to turn yellow and affecting the final yellowing resistance of the product; from Comparative Example 1, it is known that when only a free radical photoinitiator is used as a curing agent without adding a co-initiator, deep curing cannot be achieved, resulting in a significant reduction in the final curing depth of the product; in Examples 1, 2, 3, 4, 5 and Comparative Examples 1, 2, 3, the curing agent or resin type was not changed, so the final yellowing resistance did not have a significant difference.

[0147] From the comparison of the data in Table 2, it can be seen that Examples 1-3 all have good anti-settling performance, among which, compared with Example 2, the anti-settling agent Si Tengda-13956 of Example 1 has a better anti-settling effect; Comparative Example 3 has a lower anti-settling performance due to the change of the particle size ratio of titanium dioxide and the uniform use of large-particle titanium dioxide (larger particles are easier to settle in low-viscosity resins); while Examples 1, 3, 4, 5 and Comparative Examples 1, 2, 4, 5, 6 did not change the filler particle size ratio or the particle size was smaller, so the final anti-settling performance did not have a significant difference.

[0148] In summary, the UV curable white ink of the present invention can be quickly cured within 25 seconds, the maximum light curing depth can reach 300 μm, and it also has a high reflectivity of more than 94% and a high whiteness of more than 70%. The final material is relatively stable after curing, and is not easily affected by ultraviolet rays or high temperatures to cause aging or bond breaking. It has high yellowing resistance and product stability, and is suitable for industrial large-scale production. Although the embodiments of the present invention are described in conjunction with the accompanying drawings, those skilled in the art can make various modifications and variations without departing from the spirit and scope of the present invention, and such modifications and variations fall within the scope defined by the present invention.

Claims

1. A UV curable white ink, characterized in that: In parts by weight: Acrylate A: 100 parts; Acrylate B: 10-40 parts; Free radical photoinitiator: 0.1-2 parts; Filler: 20-70 parts; Additives: 0.5-10 parts; The auxiliary agent includes a co-initiator and an anti-settling agent, and the co-initiator is a tertiary amine co-initiator; The acrylate A is selected from at least one of aliphatic polyurethane acrylate, polyurethane-modified epoxy acrylate, and amine-modified epoxy acrylate; The acrylate B is selected from at least one of methacrylate phosphate, isobornyl methacrylate, and tripropylene glycol diacrylate.

2. The UV curable white ink according to claim 1, characterized in that: The viscosity of the acrylate A is 3000-20000 cp, and the viscosity of the acrylate B is 50-2000 cp.

3. The UV curable white ink according to claim 1, characterized in that: The free radical photoinitiator is selected from at least one of quinone photoinitiators, 1-hydroxy-cyclohexyl benzophenone, and bis-titanocene.

4. The UV curable white ink according to claim 1, characterized in that: The filler is selected from at least one of titanium dioxide, zinc oxide, and barium sulfate, and the particle size and mass ratio of the filler are in the range of: (0.1-0.5 μm): (0.5-1.0 μm): (1.0-2.0 μm) = (4-7): (2-4): (1-2).

5. The UV curable white ink according to claim 1, characterized in that: The weight proportions of the co-initiator and the anti-settling agent are 0.5-2 parts and 0.2-5 parts respectively.

6. The UV curable white ink according to claim 1, characterized in that: The anti-settling agent is selected from at least one of polyamide wax, ultrafine matting powder and organic bentonite.

7. The UV curable white ink according to claim 1, characterized in that: The UV curable white ink has a reflectivity of >94%, a whiteness value of >70%, a curing depth of ≥200 μm, a whiteness value difference of <3% before and after monitoring for 1000 hours under double 85 conditions, and a UV light curing time of ≤25 seconds.

8. A method for preparing the UV curable white ink according to any one of claims 1 to 7, characterized in that: The steps include: Mixing acrylate A and acrylate B in proportion to obtain a first mixed material; Adding a photoinitiator, a co-initiator and an anti-settling agent to the first mixed material to obtain a second mixed material; adding filler to the second mixed material to obtain a third mixed material; The third mixed material is ground and filtered to obtain the UV curable white ink.

9. The method for preparing UV curable white ink according to claim 8, characterized in that: Fillers of different particle sizes are mixed evenly before adding into the second mixture.

10. Application of the UV-curable white ink according to any one of claims 1 to 7 in Mini LED backlight coatings, LED displays, printed electronics, and LED lighting.